![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算:(1)[(a2)5?(-a2)3]÷(-a4)4;(2)(a-b)3÷(b-a)2+(-a-b)5÷(a+b)
计算:(1)[(a2)5?(-a2)3]÷(-a4)4;(2)(a-b)3÷(b-a)2+(-a-b)5÷(a+b)4...
计算:(1)[(a2)5?(-a2)3]÷(-a4)4;(2)(a-b)3÷(b-a)2+(-a-b)5÷(a+b)4
展开
1个回答
展开全部
(1)[(a2)5?(-a2)3]÷(-a4)4,
=[a10?(-a6)]÷a16,
=[-a16]÷a16,
=-1;
(2)(a-b)3÷(b-a)2+(-a-b)5÷(a+b)4,
=(a-b)3÷(a-b)2-(a+b)5÷(a+b)4,
=(a-b)-(a+b),
=a-b-a-b,
=-2b.
=[a10?(-a6)]÷a16,
=[-a16]÷a16,
=-1;
(2)(a-b)3÷(b-a)2+(-a-b)5÷(a+b)4,
=(a-b)3÷(a-b)2-(a+b)5÷(a+b)4,
=(a-b)-(a+b),
=a-b-a-b,
=-2b.
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询